2004
DOI: 10.1046/j.0906-6713.2002.003424.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological diagnostic testing in the treatment of periodontal diseases

Abstract: A variety of microbiological diagnostic tests are available for clinicians to use for evaluation of patients with periodontal disease. Each one has its own unique set of advantages and disadvantages, and probably the most useful information for the clinician can be obtained using a combination of the various analytic methods. The tests appear to have their greatest utility when used on patients with chronic or aggressive periodontitis who do not respond favorable to conventional mechanical therapy. The major l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
25

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 87 publications
2
99
1
25
Order By: Relevance
“…There are a number of possible explanations for this inconsistency, including differences in disease status at the sampled site and the method used to detect and estimate the copy numbers of pathogens present (41). Loomer reported that analysis of the overall oral microbiota profile of a patient is more representative when a greater number of sites is sampled (42). Thus, in this study, samples from at least five sites with the deepest pockets were collected and pooled together, which was essential in accurately characterizing subgingival microbiota in its natural niche in the deepest pockets.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of possible explanations for this inconsistency, including differences in disease status at the sampled site and the method used to detect and estimate the copy numbers of pathogens present (41). Loomer reported that analysis of the overall oral microbiota profile of a patient is more representative when a greater number of sites is sampled (42). Thus, in this study, samples from at least five sites with the deepest pockets were collected and pooled together, which was essential in accurately characterizing subgingival microbiota in its natural niche in the deepest pockets.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that different species of periodontal pathogens necessitate different sampling schemes [22]. The outcome of the analysis can further be affected by the method of sample collection [12,19].…”
Section: Samplingmentioning
confidence: 99%
“…-increased prognostic value -aids in planning appropriate therapeutic strategy -targeted antibiotic therapy -monitoring of successful periodontal therapy -allows a high level of certainty when expensive interventions such as placing dental implants and prosthetic or orthodontic rehabilitation are necessary [18].…”
Section: Benefits Of Microbiological Diagnosticsmentioning
confidence: 99%